The relationship of stress tests in achieving banking safety - an analytical study - علاء فرحان طالب; سعدي احمد الموسوي; صباح حسن عبد سلمان العكيلي (Iraqi Journal for Administrative Sciences, 2024)
This research attempted to show the relationship of stress tests in achieving bank security, A sample of the banks’ financial ratios was used to conduct the analysis. The study included a sample of UAE commercial banks and conclusions were reached indicating a strong relationship between these two variables.